Factors Affecting Muzaki’s Decision to Pay Zakat in Baznas City of Depok for the 2020 Period - Kaimiyaul gina gina fahrani (Universitas Pendidikan Indonesia, 2022)
Purpose – This study aims to determine empirically the effect of Accountability, Transparency of Zakat Management and Income Levels during the pandemic on muzaki's decisions in paying zakat at BAZNAS Depok City.Methodology - In this study, there are three independent variables, namely Accountability, Transparency, and Income Level. And has one dependent variable, namely the decision of muzaki. The population of this study is muzaki recorded at the National Amil Zakat Agency (BAZNAS) Depok City in 2020. The data used is primary data using a questionnaire technique distributed to 102 respondents. The analytical method used is multiple linear regression with SPSS tools.Findings - The results of this study indicate that simultaneously accountability, transparency, and income levels influence muzaki decisions. Partially accountability and transparency have a positive effect on muzaki decisions. While the level of income has a negative effect on the decision of muzaki in paying zakat.Keywords: Accountability, Transparency, Income Level, Pandemic Era, National Amil Zakat Agency (BAZNAS)